PENERAPAN PERATURAN BUPATI SIAK NOMOR 27TAHUN 2011 TENTANG SISTEM EVALUASI DAN PROSEDUR PENGELOLAAN BARANG MILIK DAERAH - Adha, Muhammad (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Evaluation of Application of Siak Regent Regulation No. 27 Year 2011 on Systemsand Procedures Management of the Region. This study aims to determine the extent of adoptionof the decree No. 27 of 2011 on Systems and Procedures Management of the Regional Secretariatof Siak regency 2014. Informants in this study is the Regional Secretary, the users of goods,the head of the public, the head of the land, the head the administration building, fixtures Head,Head of finance, the board of goods, storage of goods, and the auxiliary board of goods withinthe Regional Secretariat of Siak. Data were obtained by interviews, observations and collect datain the form of asset reports and documents. The method used is descriptive qualitative approachto analyze data through data reduction procedures, data and conclusion. The results showed thatthe adoption of the decree No. 27 of 2011 Siak not completely worked up because there are somecycles in the asset management area is not in accordance with existing rules.